Actions of snake neurotoxins on an insect nicotinic cholinergic synapse. - Hue, B; Buckingham, S; Buckingham, D; Sattelle, D (2007)
Here we examine the actions of six snake neurotoxins (alpha-cobratoxin from Naja naja siamensis, erabutoxin-a and b from Laticauda semifasciata; CM12 from N. haje annulifera, toxin III 4 from Notechis scutatus and a long toxin from N. haje) on nicotinic acetylcholine receptors in the cercal afferent, giant interneuron 2 synapse of the cockroach, Periplaneta americana. All toxins tested reduced responses to directly-applied ACh as well as EPSPs evoked by electrical stimulation of nerve XI with similar time courses, suggesting that their action is postsynaptic. Thus, these nicotinic receptors in a well-characterized insect synapse are sensitive to both long and short chain neurotoxins. This considerably expands the range of snake toxins that block insect nicotinic acetylcholine receptors and may enable further pharmacological distinctions between nAChR subtypes.